Vimentin Intermediate Filament Rings Deform the Nucleus During the First Steps of Adhesion - Terriac, Emmanuel; Schütz, Susanne; Lautenschläger, Franziska (Frontiers in Cell and Developmental Biology, 2019)
During cell spreading, cells undergo many changes to their architecture and their mechanical properties. Vimentin, as an integral part of the cell architecture, and its mechanical stability must adapt to the new state of the cell. This study focuses on the structures formed by vimentin during the first steps of cell adhesion. Very early, ball-like structures, or ‘knots’, are seen and often vimentin filaments emerge in the shape of rings around the nucleus. Although intermediate filaments are not known to be associated to motor proteins to form contractile systems, these rings can nonetheless strongly deform the cell nucleus. In the first 6 h to 12 h of adhesion, these vimentin knots and rings disappear, and the intermediate filament network returns to the state seen before detachment of the cells. As these vimentin structures are very transient in the early steps of cell spreading, they have rarely been described in the literature. However, they can also be seen during mitosis, which is an event that involves partial detachment and re-spreading of the cells. Interestingly, the turnover dynamics of vimentin are reduced in both the knots and rings, compared to vimentin in the lamelipodia. It remains to de defined how the force is transmitted from the ball-like structures to the rings, and to measure the impact of such strong nuclear deformation on gene expression during cell re-spreading and the rearrangement of the vimentin network.